Sir William Maxwell : a Pioneer of National and International Co-operation. - Elliott, Sydney R. (Manchester : Co-operative Union, 1923)
Bibliotheek E. Anseele
Dedicator: Britisch Co-operative Union, dedicatee: Anseele, Edward (sr.)
Engels
Monografie